Silicon-carbon negative electrode material, preparation method and application thereof, and lithium ion battery

By generating LixSiOy and/or LixSiNy layers on the surface of the silicon-based anode material, and using the coating technology of carbon nanotubes and solid carbon sources, the problems of high expansion rate and poor conductivity of the silicon-based anode material are solved, achieving higher cycle life and electrochemical performance.

CN119660747AActive Publication Date: 2025-03-21JIANGSU LIHUANG TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510172929.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-03-21
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

The existing silicon-based negative electrode materials have a high volume expansion rate during charging and discharging, resulting in the powderization of the electrode material, structural damage and repeated formation of solid electrolyte interface (SEI) film, affecting the battery circulation performance.

Method used

Using chemical vapor deposition method, LixSiOy and/or LixSiNy layers are generated on the surface of the silicon source, and silicon expansion is suppressed through the elastic network of the carbon nanotubes, combined with the coating of the solid carbon source, forming a multi-layer carbon structure with loose conductive network and external rigid carbon coating.

Benefits of technology

It effectively reduces the silicon expansion rate, improves the cycle life of the material and the first Coulomb efficiency, and enhances the electronic conductivity and interface stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660747A_ABST
    Figure CN119660747A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of silicon-carbon negative electrode materials, and discloses a silicon-carbon negative electrode material, a preparation method and application thereof, and a lithium ion battery. The method comprises the following steps: (1) soaking a silicon source in a catalyst solution, filtering, drying, mixing with lithium hydroxide, and performing high-temperature pyrolysis in a mixed gas atmosphere to obtain a precursor; the mixed gas comprises inert gas, carbon source gas, reducing gas and'oxygen group-containing gas and / or nitrogen group-containing gas', the molar ratio of the silicon source to the lithium hydroxide is 100: (0.1-5), the flow ratio of the carbon source gas is 0.5-5%, and the flow ratio of the reducing gas is 0.5-5%; the temperature of high-temperature pyrolysis is 600 to 1050 DEG C; and (2) mixing the precursor and a solid carbon source, granulating and carbonizing. The silicon-carbon negative electrode material prepared by the invention can reduce the silicon expansion rate before and after charging and discharging and prolong the cycle life of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of silicon-carbon negative electrode materials, and specifically relates to a silicon-carbon negative electrode material and a preparation method, application and a lithium ion battery thereof. Background Art

[0002] As the negative electrode material of lithium-ion batteries, silicon-based negative electrodes are considered to be the key negative electrode materials for the next generation of high energy density batteries because of their theoretical specific capacity of up to 4200mAh / g, which is much higher than that of graphite negative electrodes. However, silicon materials are currently only used for graphite doping of less than 10%, which makes it difficult to give full play to their high specific capacity characteristics. The main reason is that silicon undergoes a huge volume expansion during the charging and discharging process, which leads to the pulverization of electrode materials, the destruction of electrode structures, and the repeated formation of solid electrolyte interface (SEI) films, which seriously affects the battery cycle.

[0003] Nano-sized silicon can alleviate the stress caused by volume expansion to a certain extent due to its unique size effect, and can also be compounded with carbon to further improve its electrochemical performance. However, silicon itself has low conductivity and lithium ion diffusion rate, and the densely packed expansion of nano-silicon will still cause the overall expansion of the battery, making it difficult to meet the actual battery application needs. Summary of the invention

[0004] The technical problem solved by the present invention is to overcome the problem of poor cycle rate performance caused by high expansion rate and poor conductivity of silicon-based negative electrode materials in the prior art, and provide a silicon-carbon negative electrode material and its preparation method, application and lithium-ion battery. The silicon-carbon negative electrode material prepared by the present invention can reserve expansion space for silicon material, reduce silicon expansion rate before and after charge and discharge, and improve material cycle life.

[0005] The present invention adopts a chemical vapor deposition method, in which an inert gas, a carbon source gas, a reducing gas and a "gas containing oxygen groups and / or a gas containing nitrogen groups" are simultaneously introduced into the reaction system, and the "gas containing oxygen groups and / or a gas containing nitrogen groups" are pyrolyzed at high temperature to generate highly reactive oxygen- and nitrogen-containing free radicals that react with a silicon source and lithium hydroxide, thereby forming a layer of Li on the surface of the silicon source. x SiO y and / or Li x S N y , while the carbon source gas is catalyzed to grow into carbon nanotubes, forming a precursor with a loose elastic coating structure; among them, Li x SiO y and / or Li x S N yFormed on the surface of the silicon source, it can prevent the silicon source from being exposed on the surface, block the direct contact between the silicon source and the electrolyte, avoid the pulverization of the silicon source, and improve the interface stability and ion mobility; carbon nanotubes can fix the silicon source, disperse the silicon source, avoid agglomeration, and inhibit the expansion of the silicon source through the elastic network of carbon nanotubes, reserve expansion space for the silicon material, and reduce the silicon expansion rate before and after charging and discharging; then a solid carbon source is used to carbon-coat the surface of the precursor, so as to prepare a multi-layered carbon structure with an elastic and loose conductive network inside and a rigid carbon coating outside; further coating of the solid carbon source can prevent the pulverization of silicon particles from destroying the electron channel, and also avoid excessive infiltration of the electrolyte on the silicon surface to produce side reactions, thereby improving the material cycle life and the first coulomb efficiency; the external coating of the rigid structure carbon layer shell helps to maintain the internal elastic microstructure and prevent excessive contact between silicon and the electrolyte to cause side reactions.

[0006] The present invention solves the above technical problems through the following technical solutions: The present invention provides a method for preparing a silicon-carbon negative electrode material, which comprises the following steps: (1) After soaking the silicon source in a catalyst solution, filtering and drying, mixing it with lithium hydroxide and then pyrolyzing it at high temperature in a mixed gas atmosphere to obtain a precursor; wherein the molar ratio of the silicon source to the lithium hydroxide is 100:(0.1-5), the mixed gas includes an inert gas, a carbon source gas, a reducing gas and "a gas containing oxygen groups and / or a gas containing nitrogen groups", the inert gas accounts for 85%-99% of the flow rate of the mixed gas introduced, the carbon source gas accounts for 0.5%-5% of the flow rate of the mixed gas introduced, and the reducing gas accounts for 0.5%-5% of the flow rate of the mixed gas introduced; the temperature of the high temperature pyrolysis is 600-1050°C, and the time of the high temperature pyrolysis is 0.1h-3h; (2) The precursor and the solid carbon source are mixed in a mass ratio of (3-20):1, and then granulated and carbonized to obtain the silicon-carbon negative electrode material.

[0007] In step (1), the "oxygen-containing gas and / or nitrogen-containing gas" is pyrolyzed at high temperature to generate highly reactive oxygen- and nitrogen-containing free radicals that react with the silicon source and lithium hydroxide, thereby forming a layer of Li on the surface of the silicon source. x SiO y and / or Li x S N y , which can prevent the silicon source from being exposed on the surface, block the direct contact between the silicon source and the electrolyte, prevent the silicon source from being pulverized, and improve the interface stability and ion mobility. When the oxygen-containing gas is introduced, Li x SiO y When the nitrogen-containing gas is introduced, Li x S N y.

[0008] In step (1), the silicon source is preferably silicon and / or silicon monoxide, more preferably silicon monoxide. The particle size of the silicon source may be 30 nm-10 μm, preferably 30-300 nm, for example 200 nm.

[0009] In step (1), the catalyst is preferably an inorganic salt of a transition metal. The transition metal is preferably one or more of Fe, Ni, Cu and Co. The inorganic salt is preferably a halide, sulfate or nitrate. The halide is preferably a hydrochloride of a transition metal.

[0010] In step (1), the concentration of the catalyst solution may be 0.2-2 mol / L, preferably 0.2-1 mol / L, for example 0.5 mol / L.

[0011] In step (1), the solvent in the catalyst solution may be one or more of deionized water, ethanol, acetone, isopropanol and chloroform, such as deionized water.

[0012] In a specific embodiment, the catalyst is 0.5 mol / L NiCl 2 aqueous solution or 0.5 mol / L nickel nitrate aqueous solution.

[0013] In step (1), the molar ratio of the silicon source to the metal ions in the catalyst solution is preferably (40-120):1, such as 50:1, 60:1, 80:1 or 100:1.

[0014] In step (1), the molar ratio of the silicon source to the lithium hydroxide is preferably 100:(1-3), for example 100:2.

[0015] In step (1), the soaking time is preferably 5-30 minutes, such as 10 minutes, 15 minutes or 20 minutes. The soaking is generally carried out at room temperature. In step (1), the inert gas may be conventional in the art, such as argon, helium or nitrogen. The flow ratio of the inert gas to the mixed gas introduced is preferably 90%-99%, such as 95.5%, 96.1% or 98%. The carbon source gas is preferably one or more of natural gas, methane, acetylene and ethylene, preferably acetylene. The flow ratio of the carbon source gas to the mixed gas introduced is preferably 0.8%-3%, such as 0.98%, 1%, 1.5%, 1.91%, 1.92% or 2%. The reducing gas may be conventional in the art, generally one or more of hydrogen, carbon monoxide and hydrogen sulfide, such as hydrogen. The flow ratio of the reducing gas to the mixed gas introduced is preferably 0.8%-3%, such as 0.98%, 1%, 1.5%, 1.91%, 1.92% or 2%. The gas containing oxygen groups is preferably ethanol gas and / or methanol gas. The flow ratio of the gas containing oxygen groups to the mixed gas introduced can be 0.1%-3%, preferably 0.1%-2%, such as 0.2%, 0.4%, 0.6% or 1%. The gas containing nitrogen groups is preferably one or more of ammonia, methylamine, ethylamine and propylamine, such as ammonia. The flow ratio of the gas containing nitrogen groups to the mixed gas introduced is preferably 0.1%-2%, such as 0.5%, 0.64%, 1% or 2%. The flow ratio of the "gas containing oxygen groups and / or the gas containing nitrogen groups" to the mixed gas introduced can be 0.1%-3%. The flow rate of the mixed gas introduced can be 800-2000sccm, preferably 1000-1700sccm, such as 1530sccm, 1560sccm or 1570sccm.

[0016] When the raw material of the "oxygen-containing gas and / or nitrogen-containing gas" is a gas, it can be directly introduced into the reaction system; when the raw material of the "oxygen-containing gas and / or nitrogen-containing gas" is a liquid, it can be converted into a gas by bubbling or heating. The bubbling can be obtained, for example, by introducing part of the inert gas into the liquid raw material corresponding to the "oxygen-containing gas and / or nitrogen-containing gas" and then discharging it.

[0017] In step (1), when the raw material corresponding to the "gas containing oxygen groups and / or the gas containing nitrogen groups" is a liquid, the mixed gas is preferably obtained by the following steps: introducing a portion of the inert gas from the first gas passage; introducing the carbon source gas and the reducing gas from the second gas passage; introducing another portion of the inert gas from the third gas passage into the raw material liquid corresponding to the "gas containing oxygen groups and / or the gas containing nitrogen groups", and discharging it from the liquid by bubbling; and combining the three gases to obtain the mixed gas. The sum of the gas flow rates of the inert gas, the carbon source gas and the reducing gas may be 1000-2000sccm, preferably 1400-1800sccm. The sum of the gas flow rates of the carbon source gas and the reducing gas may be 20-100sccm, for example 30sccm or 60sccm. The ratio of the gas flow rates of the carbon source gas and the reducing gas may be 1:(0.5-2), for example 1:1. The carbon source gas accounts for 0.8%-3% of the sum of the gas flow rates of the inert gas, the carbon source gas and the reducing gas, for example, 0.98%, 1%, 1.5%, 1.92% or 2%. The reducing gas accounts for 0.8%-3% of the sum of the gas flow rates of the inert gas, the carbon source gas and the reducing gas, for example, 0.98%, 1%, 1.5%, 1.92% or 2%. The amount of inert gas introduced from the third gas passage accounts for 20-40% of the total gas flow rate of the inert gas, for example, 33.3%. The volume of the raw material liquid corresponding to the "oxygen-containing group gas and / or nitrogen-containing group gas" can be 200-1000mL, for example, 500mL.

[0018] In step (1), when the raw material corresponding to the "gas containing oxygen groups and / or the gas containing nitrogen groups" is gas, the mixed gas is preferably obtained by the following steps: introducing the inert gas from a first gas passage; introducing the carbon source gas and the reducing gas from a second gas passage; introducing the "gas containing oxygen groups and / or the gas containing nitrogen groups" from a third gas passage; and combining the three gases to obtain the mixed gas.

[0019] In step (1), according to the common practice in the art, the high-temperature pyrolysis is generally carried out in a tube furnace.

[0020] In step (1), the temperature of the high-temperature pyrolysis is preferably 700-900°C, for example, 800°C. The time of the high-temperature pyrolysis may be 0.1h-2h, for example, 0.2h or 0.5h, preferably 0.3-1h. The rate of heating to the temperature of the high-temperature pyrolysis may be 2-10°C / min; preferably 3-5°C / min. The process of heating to the temperature of the high-temperature pyrolysis is generally carried out under an inert gas atmosphere. The inert gas flow rate may be 1000-2000sccm. According to the convention in the art, after the high-temperature pyrolysis is completed, it is generally necessary to cool naturally to room temperature.

[0021] According to the common practice in the art, the temperature is generally first raised to the high-temperature pyrolysis temperature in an inert gas atmosphere, and then the inert gas is switched to the mixed gas, and the high-temperature pyrolysis is carried out in the atmosphere of the mixed gas.

[0022] In step (2), the solid carbon source may be one or more of asphalt, petroleum coke and phenolic resin, preferably asphalt. The mass ratio of the precursor to the solid carbon source is preferably (5-20):1, such as 10:1 or 15:1.

[0023] In step (2), the granulation is preferably spray granulation. The operation and conditions of the spray granulation may be conventional in the art. Before the spray granulation, it is generally necessary to first prepare the mixture of the precursor and the solid carbon source into a slurry, and then pump the slurry into a spray granulator for spray granulation. The components of the slurry may include a mixture of the precursor and the solid carbon source, deionized water and PVP. In terms of weight fraction, the mixture of the precursor and the solid carbon source: deionized water: PVP may be (60-80): (90-110): (3-10), for example 70:100:5. Before the spray granulation, it is generally necessary to mix the slurry evenly. The process parameters of the spray granulation may be an air inlet temperature of 170-220°C (for example 190°C) and an air outlet temperature of 80-110°C (for example 95°C).

[0024] In step (2), the carbonization is generally carried out in a tube furnace. According to the conventional art, the carbonization is generally carried out under the protection of an inert gas. The inert gas is, for example, nitrogen or argon.

[0025] In step (2), the carbonization temperature may be 300-800° C., such as 400° C., 500° C. or 600° C. The carbonization time may be 0.5 h to 3 h, such as 1 h or 2 h.

[0026] The present invention also provides a silicon-carbon negative electrode material prepared by the preparation method as described above.

[0027] In the present invention, the silicon-carbon negative electrode material is preferably in the form of microspheres. The size of the silicon-carbon negative electrode material may be 2-50 μm.

[0028] In the present invention, the silicon-carbon negative electrode material generally has a core-shell structure, the core of which includes a silicon source, "Li x SiO y and / or Li x S N y " and carbon nanotubes, the shell is amorphous carbon; in the core, "Li x SiO y and / or Li x S N y " is coated on the surface of the silicon source, and the carbon nanotubes are coated on the "Li x SiO y and / or Li x S N y ” surface.

[0029] Wherein, the silicon source may be silicon and / or silicon 2 oxide. The particle size of the silicon source may be 30nm-10μm, preferably 30-300nm. x SiO y and / or Li x S N y The coating thickness of the carbon nanotubes may be 30-500 nm. The coating thickness of the amorphous carbon may be 100-800 nm.

[0030] Among them, the Li x SiO y Preferably, 1<x<4, 0.5<y<2.

[0031] Among them, the Li x S N y Preferably, 1<x<8, 0.5<y<4.

[0032] The present invention also provides an application of the silicon-carbon negative electrode material as described above in a lithium-ion battery.

[0033] The present invention also provides a lithium ion battery, which comprises a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode comprises the silicon-carbon negative electrode material as described above.

[0034] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0035] The reagents and raw materials used in the present invention are commercially available.

[0036] The positive and progressive effects of the present invention are: The silicon-carbon negative electrode material prepared by the present invention can prevent the silicon source from being exposed on the surface, block the direct contact between the silicon source and the electrolyte, avoid the pulverization of the silicon source, reserve expansion space for the silicon material, and reduce the silicon expansion rate before and after charging and discharging; it is applied to lithium-ion batteries and has good electronic conductivity and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 A schematic diagram of the structure of the silicon-carbon negative electrode material prepared in Example 1-9; Figure 2 This is a SEM image of the silicon-carbon negative electrode material prepared in Example 5; Figure 3 Part (a) is a SEM image of a ground and pulverized sample of the silicon-carbon negative electrode material prepared in Example 5; Figure 3 Part (b) is a SEM image of the local internal structure of the ground and pulverized sample of the silicon-carbon negative electrode material prepared in Example 5; Figure 4 This is the XRD pattern of the silicon-carbon negative electrode material prepared in Example 5.

[0038] Reference numerals Silicon source 1 Li x SiO y and / or Li x S N y 2 Carbon Nanotubes 3 Amorphous Carbon 4 DETAILED DESCRIPTION

[0039] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0040] The silicon powder used in the following examples and comparative examples was purchased from Aladdin, and had a purity of 99.9% and a particle size of about 1 μm.

[0041] Example 1

[0042] (1) Immerse silicon powder in 0.5M NiCl at room temperature 2 After immersion in aqueous solution for 10 minutes (silicon powder and NiCl 2 Ni in aqueous solution 2+The molar ratio of silicon powder to lithium hydroxide is 50:1), filtered, dried and mixed with lithium hydroxide, the molar ratio of silicon powder to lithium hydroxide is 100:2, the two are mixed evenly and put into a crucible, added into a tube furnace, and the first gas Ar is introduced at a flow rate of 1000sccm, and heated to 800°C at a heating rate of 5°C / min in an Ar atmosphere; then, while maintaining the first gas Ar continuously introduced at a flow rate of 1000sccm, the second gas and the third gas are introduced, the second gas is 30sccm of acetylene and 30sccm of hydrogen; the third gas is 500sccm The third Ar is introduced from the gas inlet of a gas collecting bottle containing 500 mL of ethanol (analytical grade, ambient temperature is 25°C) and discharged from the gas outlet of the gas collecting bottle, thereby taking the ethanol out of the gas collecting bottle, and the three gases are combined to obtain a mixed gas and introduced into a tubular furnace, and the mixed gas of the above three gases is continuously introduced at 800°C for 0.5h, and after cooling to room temperature, a precursor A is obtained; The connection method of the three-way gas passage is shown in the following literature Figure 1 :Study on the preparation of graphene film by low hydrogen atmospheric pressure CVD method with ethanol as carbon source and its growth mechanism, Li Liang et al., Atomic Energy Science and Technology, Vol. 49, No. 3.

[0043] (2) Precursor A and asphalt (Shandong Shouhua Chemical Co., Ltd., softening point 60°C~90°C, 98%) were mixed in a mass ratio of 10:1 to obtain a mixture; 70 parts of the mixture, 100 parts of deionized water, and 5 parts of PVP-K30 were added to the mixer in sequence by weight and stirred to obtain a precursor slurry; the precursor slurry was pumped into a spray granulator and spray granulated at an air inlet temperature of 190°C and an air outlet temperature of 95°C to obtain a precursor B; the precursor B was heated to 500°C at a heating rate of 3°C / min in a tubular furnace in a nitrogen atmosphere, kept warm for 1 hour, and then cooled to room temperature to obtain a silicon-carbon negative electrode material.

[0044] Example 2 Compared with Example 1, except that acetylene in step (1) is replaced by natural gas (Sichuan Zhongce, standard gas, industrial grade), and the heating temperature is replaced from 800° C. to 1000° C., the other parameters and conditions are the same as those in Example 1.

[0045] Example 3 Compared with Example 1, except that the heating time in step (1) is replaced from 0.5 h to 0.2 h, the other parameters and conditions are the same as those in Example 1.

[0046] Example 4 Compared with Example 1, except that the second gas in step (1) is adjusted to 15 sccm of acetylene and 15 sccm of hydrogen, the other parameters and conditions are the same as those in Example 1.

[0047] Example 5 Compared with Example 1, except that the silicon powder is replaced by sand-ground silicon powder (the silicon powder is sand-ground in an ethanol medium to a diameter of about 200 nm), the other parameters and conditions are the same as those in Example 1.

[0048] Example 6 Compared with Example 1, except that silicon powder is replaced by silicon oxide powder (Shanghai Maoguo, particle size 1 μm, purity 99.9%), other parameters and conditions are the same as those in Example 1.

[0049] Example 7 Compared with Example 1, except that the asphalt in step (2) is replaced by petroleum coke (Hebei Houkang, low-sulfur coke), the other parameters and conditions are the same as those in Example 1.

[0050] Example 8 Compared with Example 1, except that the asphalt in step (2) is replaced by phenolic resin (Shandong Guohua Chemical, melting point 94° C., water-soluble), the other parameters and conditions are the same as those in Example 1.

[0051] Example 9 Step (1): Immerse silicon powder in 0.5M NiCl at room temperature. 2 After immersion in aqueous solution for 10 minutes (silicon powder and NiCl 2 Ni in aqueous solution 2+ The molar ratio is 50:1), filtered, dried, put into a crucible, added into a tube furnace, introduced into a first gas Ar at a flow rate of 1500sccm, heated to 800°C at a heating rate of 5°C / min in an argon atmosphere; then, while maintaining the first gas Ar at a flow rate of 1500sccm, introduced into a second gas and a third gas, the second gas is 30sccm of acetylene and 30sccm of hydrogen, the third gas is 10sccm of ammonia, the three gases are combined to obtain a mixed gas, the mixed gas of the three gases is continuously introduced at 800°C for 0.5h, and the precursor A is obtained after cooling to room temperature; Step (2): Same as Example 1.

[0052] Comparative Example 1 Silica powder.

[0053] Comparative Example 2 Precursor A in Example 1.

[0054] Comparative Example 3 Silicon powder and asphalt (Shandong Shouhua Chemical Co., Ltd., softening point 60℃~90℃, 98%) were mixed in a mass ratio of 10:1, heated to 500℃ at a heating rate of 3℃ / min in a tubular furnace in a nitrogen atmosphere, kept warm for 1h, and then cooled to room temperature to obtain a silicon-carbon negative electrode material.

[0055] Comparative Example 4 Step (1): Immerse silicon powder in 0.5M NiCl at room temperature. 2 After immersion in aqueous solution for 10 minutes (silicon powder and NiCl 2 Ni in aqueous solution 2+ The molar ratio is 50:1), filtered, dried, put into a crucible, added into a tube furnace, introduced into a first gas Ar at a flow rate of 1500sccm, and heated to 800°C at a heating rate of 5°C / min in an argon atmosphere; then, while maintaining the first gas Ar at a flow rate of 1500sccm, introduced into a second gas, the second gas being 30sccm of acetylene and 30sccm of hydrogen, the two gases are combined to obtain a mixed gas and introduced into the tube furnace; the mixed gas of the above two gases is continuously introduced at 800°C for 0.5h, and after cooling to room temperature, a precursor A is obtained; Step (2): Same as Example 1.

[0056] Effect Example (1) Morphology characterization and XRD testing The structural schematic diagram of the silicon-carbon negative electrode material prepared in Examples 1-9 of the present invention is as follows Figure 1 As shown, the silicon-carbon negative electrode material has a core-shell structure, the core includes a silicon source 1, "Li x SiO y and / or Li x S N y ” 2 and carbon nanotubes 3, the outer shell is amorphous carbon 4; in the core, “Li x SiO y and / or Li x S N y "2 is coated on the surface of silicon source 1, and carbon nanotubes 3 are coated on "Li x SiO y and / or Li x S N y ”2. The silicon source may be silicon and / or silicon monoxide. The particle size of the silicon source may be 30nm-10μm. Li x SiO y Layer and / or Li x S N y The thickness of the layer can be 1-10 nm. x SiO y In, 1<x<4, 0.5<y<2. Lix S N y 1<x<8, 0.5<y<4. The coating thickness of the carbon nanotubes may be 30-500 nm. The coating thickness of the amorphous carbon may be 100-800 nm.

[0057] Figure 2 This is the SEM image of the silicon-carbon negative electrode material prepared in Example 5. Figure 2 It can be seen that the prepared silicon-carbon negative electrode material is microspherical with a size of 2-50μm. Figure 3 Part (a) is a SEM image of a ground and pulverized sample of the silicon-carbon negative electrode material prepared in Example 5; Figure 3 Part (b) is a SEM image of the local internal structure of the ground and pulverized sample of the silicon-carbon negative electrode material prepared in Example 5. From the image, it can be seen that the three-dimensional carbon tube network structure is wrapped around the surface of the nano-silicon particles. Figure 4 This is the XRD diagram of the silicon-carbon negative electrode material prepared in Example 1.

[0058] (2) Electrochemical performance test The silicon-carbon negative electrode materials prepared in Examples 1 to 9 and the materials prepared in Comparative Examples 1 to 4 were subjected to half-cell tests. The test method is: the above-mentioned materials to be tested are uniformly mixed with the binder CMC (sodium carboxymethyl cellulose) and the conductive carbon black in a mass ratio of 85:5:10, adjusted into a slurry, coated on a copper foil with a coating thickness of 100 microns, and dried at 90°C in vacuum for 12 hours to prepare a lithium battery negative electrode sheet. The simulated battery assembly was carried out in an argon-filled glove box, using 1 mol / L LiPF 6 The electrolyte (solvent is EC, EMC and DMC, EC: EMC: DMC = 1:1:1 (volume ratio), polypropylene microporous membrane is used as the separator, and metal lithium sheet is used as the counter electrode. The electrochemical performance test was carried out on a Land CT2001A battery tester at a temperature of 20 °C and a charge and discharge voltage range of 0.01 to 1.5 V (1 C = 250 mAh g −1 ). The test results are shown in Table 1.

[0059] Table 1

[0060] According to the above experimental results, the silicon-carbon negative electrode material prepared in the present invention has excellent electrochemical properties, especially has better specific capacity and cycle life.

[0061] According to Example 1 and Comparative Example 4, when ethanol is not introduced into the mixed gas, the initial charge specific capacity and the capacity retention rate after 100 cycles of the prepared silicon-carbon negative electrode material are significantly reduced.

[0062] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A method for preparing a silicon-carbon negative electrode material, characterized in that: The following steps are involved: (1) After soaking the silicon source in a catalyst solution, filtering and drying, the silicon source is mixed with lithium hydroxide and then subjected to high-temperature pyrolysis in a mixed gas atmosphere to obtain a precursor; wherein the molar ratio of the silicon source to the lithium hydroxide is 100:(0.1-5), the mixed gas comprises an inert gas, a carbon source gas, a reducing gas and "a gas containing oxygen groups and / or a gas containing nitrogen groups", the inert gas accounts for 85%-99% of the flow rate of the mixed gas, the carbon source gas accounts for 0.5%-5% of the flow rate of the mixed gas, and the reducing gas accounts for 0.5%-5% of the flow rate of the mixed gas; the temperature of the high-temperature pyrolysis is 600-1050°C, and the time of the high-temperature pyrolysis is 0.1h-3h; (2) The precursor and the solid carbon source are mixed in a mass ratio of (3-20):1, and then granulated and carbonized to obtain the silicon-carbon negative electrode material.

2. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: The mixed gas meets one or more of the following conditions: (1) The inert gas is argon, helium or nitrogen; (2) The carbon source gas is one or more of natural gas, methane, acetylene and ethylene; (3) The flow rate ratio of the carbon source gas to the introduced mixed gas is 0.8%-3%; (4) The reducing gas is one or more of hydrogen, carbon monoxide and hydrogen sulfide; (5) The flow rate ratio of the reducing gas to the introduced mixed gas is 0.8%-3%; (6) The flow rate ratio of the "gas containing oxygen groups and / or the gas containing nitrogen groups" to the introduced mixed gas is 0.1%-3%; (7) The gas containing oxygen groups is ethanol gas and / or methanol gas; (8) The nitrogen-containing gas is one or more of ammonia, methylamine, ethylamine and propylamine; (9) The flow rate of the mixed gas is 800-2000sccm; (10) The flow ratio of the inert gas to the introduced mixed gas is 90%-99%.

3. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: Step (1) Satisfy one or more of the following conditions: (1) The silicon source is silicon and / or silicon monoxide; (2) The particle size of the silicon source is 30nm-10μm; (3) The catalyst is an inorganic salt of a transition metal; (4) The concentration of the catalyst solution is 0.2-2 mol / L; (5) The solvent in the catalyst solution is one or more of deionized water, ethanol, acetone, isopropanol and chloroform; (6) The molar ratio of the silicon source to the lithium hydroxide is 100:(1-3).

4. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: Step (1) satisfies one or more of the following conditions: (1) The molar ratio of the silicon source to the metal ions in the catalyst solution is (40-120):1; (2) The soaking time is 5-30 minutes; (3) The temperature of the high temperature pyrolysis is 700-900°C; (4) The high temperature pyrolysis time is 0.1h-2h.

5. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: When the raw material corresponding to the "gas containing oxygen groups and / or the gas containing nitrogen groups" is liquid, the mixed gas is obtained by the following steps: introducing a part of the inert gas from the first gas passage; introducing the carbon source gas and the reducing gas from the second gas passage; introducing another part of the inert gas from the third gas passage into the raw material liquid corresponding to the "gas containing oxygen groups and / or the gas containing nitrogen groups", and discharging from the liquid by bubbling; combining the three gases to obtain the mixed gas; When the raw material corresponding to the "gas containing oxygen groups and / or gas containing nitrogen groups" is gas, the mixed gas is preferably obtained through the following steps: introducing the inert gas from the first gas passage; introducing the carbon source gas and the reducing gas from the second gas passage; introducing the "gas containing oxygen groups and / or gas containing nitrogen groups" from the third gas passage; and combining the three gases to obtain the mixed gas.

6. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: Step (2) satisfies one or more of the following conditions: (1) The solid carbon source is one or more of asphalt, petroleum coke and phenolic resin; (2) The mass ratio of the precursor to the solid carbon source is (5-20): 1; (3) The carbonization temperature is 300-800°C; (4) The carbonization time is 0.5h~3h; (5) The granulation is spray granulation.

7. The method for preparing the silicon-carbon negative electrode material according to claim 6, characterized in that: Before the spray granulation, the mixture of the precursor and the solid carbon source is first made into a slurry, and then the slurry is pumped into a spray granulator for spray granulation; And / or, the process parameters of the spray granulation are an air inlet temperature of 170-220°C and an air outlet temperature of 80-110°C.

8. A silicon-carbon negative electrode material, characterized in that: It is prepared according to the method for preparing the silicon-carbon negative electrode material as described in any one of claims 1 to 7.

9. Use of the silicon-carbon negative electrode material as claimed in claim 8 in a lithium-ion battery.

10. A lithium ion battery, characterized in that: It comprises a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode comprises the silicon-carbon negative electrode material as claimed in claim 8.

Citation Information

Patent Citations

  • Silicon-carbon negative electrode material, preparation method and application

    CN113659122A

  • Method for preparing silicon-carbon negative electrode by combining sanding with spray drying

    CN117199264A

  • Silicon negative electrode material with double coating layers as well as preparation method and application of silicon negative electrode material

    CN118888722A

  • Silicon-carbon negative electrode material, preparation method and application thereof, and battery

    CN119419251A